N-Aroyloxycarbamates as switchable nitrogen and oxygen precursor: Ir/Cu controlled divergent C–H functionalization of heteroarenes. Issue 8 (2nd March 2022) - Liu, Shanshan; Zhang, Yuanyuan; Zhao, Chen; Zhou, Xianying; Liang, Jiahui; Zhang, Pingjun; Jiao, Lin-Yu; Yang, Xiufang; Ma, Yangmin
Abstract : Chemodivergent control in the functionalization of nitrogen-directed aromatic C–H bonds has been achieved by a switchable catalyst. Abstract : Chemodivergent control in the functionalization of nitrogen-directed aromatic C–H bonds has been achieved by a switchable catalyst. Specifically, under an Ir/ionic liquid (IL) catalytic system, the sustainable amidation reaction was realized by utilizing N -aroyloxycarbomate as an amino precursor. Conversely, a distinct new reactivity of this reagent was explored under a copper system as the oxygen source by the removal of a nitrogen fragment. As a benefit of this new reactivity, cascade aroyloxylation and difluoroboronation of heteroarenes was also achieved to straightforward and modular access structure diversified N, O -bidentate organic BF2 complexes under external-oxidant-free conditions. The combination of versatile transformations, high functional group tolerance, easy derivation, simple operation, and environmentally friendly reaction conditions emphasizes the importance of the current transformations. Based on a series of control experiments, a dual catalytic mechanism was proposed to account for the product diversity.